Nivolumab treatment for oesophageal squamous-cell carcinoma: an open-label, multicentre, phase 2 trial. Issue 5 (May 2017) - Kudo, Toshihiro; Hamamoto, Yasuo; Kato, Ken; Ura, Takashi; Kojima, Takashi; Tsushima, Takahiro; Hironaka, Shuichi; Hara, Hiroki; Satoh, Taroh; Iwasa, Satoru; Muro, Kei; Yasui, Hirofumi; et al.
Summary: Background: Nivolumab is a human monoclonal IgG4 antibody that inhibits programmed cell death protein 1 (PD-1) expressed on activated T cells. We investigated the safety and activity of nivolumab in patients with treatment-refractory oesophageal cancer. Methods: We did an open-label, single-arm, multicentre phase 2 study. Eligible patients had advanced squamous-cell carcinoma, adenosquamous-cell carcinoma, or adenocarcinoma of the oesophagus refractory or intolerant to fluoropyrimidine-based, platinum-based, and taxane-based chemotherapy. Patients were treated with 3 mg/kg nivolumab given intravenously once every 2 weeks in 6-week cycles. The primary endpoint was centrally assessed objective response (the proportion of patients whose best response was complete or partial response), according to the Response Evaluation Criteria In Solid Tumors, version 1.1. Adverse events and treatment-related adverse events (defined as events for which a causal relation to nivolumab could not be ruled out) were monitored throughout the study. The safety analysis was done in patients who received at least one dose of nivolumab, and drug activity was assessed in patients who received at least one dose of nivolumab and had at least one central assessment of tumour response. This study is registered with clinicaltrials.jp, number ONO-4538-07/JapicCTI-No.142422. Follow-up of patients is ongoing. Findings: Between Feb 25 and Nov 14, 2014, 65 patients were enrolled, all with squamous-cell carcinoma. 64 patients were assessable for the primary endpoint as one patient was excluded due to having multiple primary cancers; all patients were assessable for safety. Median follow-up was 10·8 months (IQR 4·9–14·3). 11 (17%, 95% CI 10–28) of 64 patients had a centrally assessed objective response. Of the 65 patients assessed for adverse events, the most common grade 3 or 4 events were grade 4 dyspnoea and hyponatraemia (one [2%) patient each), grade 3 lung infection (five [8%] patients), grade 3 decreased appetite (two [3%] patients), grade 3 increased blood creatinine phosphokinase (two [3%] patients), and grade 3 dehydration (two [3%] patients). Serious adverse events that occurred during the study were lung infection (four [6%] patients), dehydration (two [3%]), interstitial lung disease (two [3%]), and hyponatraemia, dyspnoea, fatigue, abnormal hepatic function, diarrhoea, bile duct stenosis, gastroenteritis, pneumonia, oedema, and back pain (one [2%] patient each). There were no treatment-related deaths. Interpretation: Nivolumab showed promising activity with a manageable safety profile. This drug could offer a potential new treatment approach for patients with treatment-refractory advanced squamous-cell carcinoma. Funding: Ono Pharmaceutical, Bristol-Myers Squibb.